Relinquishing business ethics from a theoretical deadlock: the requirement for local grounding and historical comparisons in the Asia Pacific region. Issue 3 (2nd July 2016) - Rowley, Chris; Oh, Ingyu
Abstract: Non-Western cases of business ethics require additional caveats in arriving at generalizations. The theoretical trap of conceiving Asian corporations as business ethics 'ignorant' or unfriendly derives from the lack of historical understanding of Asian cases. This collection used both historical and contemporary cases of Japan, Korea and China to show that these three Asian cases have tried to balance their traditional norms and values of business ethics with those from the West. The key to the understanding of Asia is that all three countries have historically pursued ethical mandates in running private corporations, although corruptive practices were also rampant during different historical periods. Further studies of business ethics for non-Western cases are necessary to devise methodological and theoretical alternatives to the Western-centric perspectives. In this volume, we analysed how new institutionalism and modes of exchange fared in their attempt to explain Asian business ethics. From our results, it is indicated that historical methods must accompany any analysis of business ethics.